2018
DOI: 10.1111/cdev.13139
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Packaging of a STEM Toy Influences Children's Play, Mechanical Learning, and Mothers’ Play Guidance

Abstract: To study effects of the gender-packaging of science, technology, engineering, and mathematics (STEM) toys, mother-child dyads (31 daughters; 30 sons; M = 5.2 years) were randomly assigned to play with a mechanical toy packaged for girls (GoldieBlox) or boys (BobbyBlox). When familiarizing themselves with the toy to prepare for play, mothers given BobbyBlox built more with toy pieces than did mothers given GoldieBlox. During dyadic play, mothers with sons built more; mothers with daughters read the toy's narrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 43 publications
0
13
1
1
Order By: Relevance
“…In our classroom observation, as compared with boys, girls were more silent in the process of solving problems, which could help them think more deeply. However, this finding was inconsistent with the previous findings that STEM was one domain where the gender divide was particularly severe (Hill, Corbett, & St Rose, 2010), and that the male advantage in the STEM areas began early and persisted throughout the life span (Coyle & Liben, 2020). Similarly, gender‐specific skills and related educational pursuits and vocational interests started early, even before preschool (Fulcher, Sutfin, & Patterson, 2008).…”
Section: Discussioncontrasting
confidence: 83%
“…In our classroom observation, as compared with boys, girls were more silent in the process of solving problems, which could help them think more deeply. However, this finding was inconsistent with the previous findings that STEM was one domain where the gender divide was particularly severe (Hill, Corbett, & St Rose, 2010), and that the male advantage in the STEM areas began early and persisted throughout the life span (Coyle & Liben, 2020). Similarly, gender‐specific skills and related educational pursuits and vocational interests started early, even before preschool (Fulcher, Sutfin, & Patterson, 2008).…”
Section: Discussioncontrasting
confidence: 83%
“…Gender‐stereotyped toys provided different types of affordances for children's exploratory play, with building and block toys allowing for engineering‐related exploration, while doll play invites exploration through pretend play and social interaction. In a recent study, Coyle and Liben () tested a gendered building toy marketed to girls (GoldieBlox) and compared it to a version they created that was named to suggest that it was a stereotypical boys' toy (BobbyBlox). They found evidence that marketing changed children's learning.…”
Section: Exploratory Play and Causal Thinkingmentioning
confidence: 99%
“…In a study with older children (11‐ to 13‐year‐olds), Tenenbaum and Leaper () found that parents believed science was more difficult and less interesting for their daughters than for their sons, despite the fact that there were no gender differences in children's science grades or expressed interest in science. Also, in the Coyle and Liben () article discussed earlier, parents talked differently to girls and boys about the STEM‐related toys, focusing more on reading the narrative instructions with girls and on building with boys. As with exploring, previous research on explaining in parent–child conversation makes clear that children's gender is an important variable to consider in our analyses.…”
Section: Explanatory Conversation and Causal Thinkingmentioning
confidence: 99%
“…And there is evidence that the types of toys with which children play might bring about specific types of behaviors. In fact, researchers have even suggested that gender differences in spatial abilities might be attributable to differences in the toys parents select for girls versus boys ( Todd et al, 2016 ; Coyle and Liben, 2020 ).…”
Section: Introductionmentioning
confidence: 99%